2020
DOI: 10.1186/s12920-020-00839-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biological correlates associated with respiratory failure in COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) is a global public health concern. Recently, a genome-wide association study (GWAS) was performed with participants recruited from Italy and Spain by an international consortium group. Methods Summary GWAS statistics for 1610 patients with COVID-19 respiratory failure and 2205 controls were downloaded. In the current study, we analyzed the summary statistics with the information of loci and p-values f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The CCR5 Δ32 variant produces a truncated protein and observably decreases receptor formulation, suppressing the immune response 82 , which may lead to increased virus susceptibility. A bioinformatics study has analysed the summary statistics of the GWAS dataset from patients with respiratory failure of COVID-19 and found that the first 10 BP involved the CCR5 83 . In an epidemiological study, CCR5 Δ32 allele frequency positively correlated with COVID-19 mortality 84 , suggesting CCR5 plays an important role in susceptibility and severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The CCR5 Δ32 variant produces a truncated protein and observably decreases receptor formulation, suppressing the immune response 82 , which may lead to increased virus susceptibility. A bioinformatics study has analysed the summary statistics of the GWAS dataset from patients with respiratory failure of COVID-19 and found that the first 10 BP involved the CCR5 83 . In an epidemiological study, CCR5 Δ32 allele frequency positively correlated with COVID-19 mortality 84 , suggesting CCR5 plays an important role in susceptibility and severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes ultra-rare, rare and common human variants, haplotypes, and susceptibility gene polymorphisms detected in several studies, through various approaches [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediator subunit gene MED23 has emerged before in SARS-CoV-2 screens, with a critical role of this complex during infection and death suggested [77]. GATA4 has been observed previously in the context of the top significant biological processes likely associated with respiratory failure in COVID-19 patients [78].…”
Section: Ratio Testmentioning
confidence: 88%